The Importance of Upper Pouch Contrast X-ray Radiography in Esophageal Atresia: A Retrospective Analysis - Sefa Sağ; Tuğçe Merve Orbay; Cengiz Gül; Ayşenur Celayir (Galenos Publishing House, 2022)
Objective: To investigate the effectiveness of preoperative upper pouch radiography in determining the treatment method in neonates with esophageal atresia (EA) and also to analyze the contribution of radiographic assessment of upper esophageal level to the prediction of anastomotic tension. Method: Neonates who underwent primary esophagus repair due to EA with distal fistula between 2014 and 2020 were analyzed retrospectively. Upper esophageal levels assessed on preoperative upper pouch radiographs and during surgery were compared. Results: A total of 36 cases were included in the study. Contrast-enhanced upper pouch radiograms were obtained using a thin catheter in 18 (50%) patients and using a thick catheter in 18 (50%) patients. The upper esophageal levels of preoperative pouch radiographs and surgery were consistent in 80.5% (n=29) and not consistent in 19.5%. The rate of compliance between radiographic and intraoperative levels was found to be significantly higher in the use of thick catheters compared to thin catheters (p=0.03). Six patients (16.6%) whose upper pouch level was in the 1st or 2nd thoracic vertebra had tense anastomosis. Conclusion: Withdrawing the upper pouch radiography by advancing a thick catheter is effective for determining the actual level of the upper esophagus. If the upper esophageal pouch is at the 1st or 2nd thoracic level on the radiographs obtained with a thick catheter, it can be predicted that the anastomosis will be tense.